Striving to be resilient: the role of crop-poultry integrated system as a climate change adaptation strategy in semiarid eastern Kenya - Kelvin Mulungu; Daniel Kangogo (Heliyon, 2022)
Climate change continues to pose significant challenges to food security and livelihoods of smallholder farmers specifically in semi-arid regions. One approach that holds prospects for climate risk management is climate-smart agriculture (CSA). CSA has concentrated on crop practices with little attention to livestock especially indigenous (village) chickens as a potential practice that can be combined with crop agriculture. This study considers the adoption of three CSA practices: improved maize seeds (IS), soil management (SM), indigenous chicken (IC) enterprise and their various combinations. Using survey data collected from 300 farming households in semiarid Kenya, we estimate the impact of integrated crop-poultry system adoption on food security and farm income using multinomial endogenous treatment effect models. Robustness checks are conducted using alternative identification strategies. Results show that, generally, the adoption of IS, SM, IC and their combinations reduces the number of months without enough food and increases farm income. When we consider the magnitude of the impacts, interesting results emerge when a combination of the CSA practices are considered. The highest impact is observed with the joint adoption of SM & IC and IS &IC. Broadly, the empirical findings suggest that integrated systems (in our case crop-poultry integration), deserve both policy and research attention as they provide synergistic benefits that improve climate resilience and household welfare.